2020
DOI: 10.1016/j.bja.2020.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Neuroactive steroids alphaxalone and CDNC24 are effective hypnotics and potentiators of GABAA currents, but are not neurotoxic to the developing rat brain

Abstract: Background: The most currently used general anaesthetics are potent potentiators of g-aminobutyric acid A (GABA A ) receptors and are invariably neurotoxic during the early stages of brain development in preclinical animal models. As causality between GABA A potentiation and anaesthetic-induced developmental neurotoxicity has not been established, the question remains whether GABAergic activity is crucial for promoting/enhancing neurotoxicity. Using the neurosteroid analogue, (3a,5a)-3-hydroxy-13,24-cyclo-18,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…The neuroactive steroids were dissolved in 15% 2-Hydroxypropyl-β-cyclodextrin solution in pH-balanced saline (pH = 7.4 to avoid tissue irritation). In our published studies, using in vitro recordings, we established that the effects of these neuroactive steroids on T-channels and GABA A receptors are within the same concentration range [ 17 , 24 ]. Hence, for that reason, we used the same range of doses of neuroactive steroids for intrathecal injections in our in vivo studies.…”
Section: Methodsmentioning
confidence: 99%
“…The neuroactive steroids were dissolved in 15% 2-Hydroxypropyl-β-cyclodextrin solution in pH-balanced saline (pH = 7.4 to avoid tissue irritation). In our published studies, using in vitro recordings, we established that the effects of these neuroactive steroids on T-channels and GABA A receptors are within the same concentration range [ 17 , 24 ]. Hence, for that reason, we used the same range of doses of neuroactive steroids for intrathecal injections in our in vivo studies.…”
Section: Methodsmentioning
confidence: 99%
“…10 Previous studies have shown that propofol is the most effective agent to activate the tonic γaminobutyric acid type A (GABA-A) current in the immature hypothalamus. The upregulation of tonic GABA-A conductance is related to epilepsy and neurodevelopmental disorders and may also contribute to memory disorders after GA. 3 Brain-derived neurotrophic factor (BDNF) is an important member of the neuron growth factor family that is widely expressed in the central nervous hippocampal system. 12,13 Research on the effects of neurotrophins in animals was useful to understanding the role of BDNF in branching, synaptic differentiation, pruning, and structural changes.…”
Section: Introductionmentioning
confidence: 99%
“… 2 As the use of anesthesia is inevitable in the clinical environment, anesthesiologists strive to find ways to assure the safety of children and provide comfort during painful procedures. 3 To minimize risks, the effects of anesthetics on the neurological system need to be understood. 4 The development of the neurological system requires a series of elaborately complicated processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An aqueous formulation of alfaxalone (Phaxan™) has been developed for use as an intravenous sedative and anesthetic 12;13 . This development occurs at a time when most commonly-used anesthetics are under investigation for neurotoxic effects [14][15][16] . Alfaxalone differs from those commonly used anesthetics in that it is a structural analogue of a naturally occurring neuroprotective hormone, allopregnanolone.…”
Section: Introductionmentioning
confidence: 99%